Targeted trapping of endogenous endothelial progenitor cells for myocardial ischemic injury repair through neutrophil-mediated SPIO nanoparticle-conjugated CD34 antibody delivery and imaging. (1st July 2022) - Sun, Ran; Wang, Xuedong; Nie, Yu; Hu, Ao; Liu, Hanrui; Zhang, Kun; Zhang, Lu; Wu, Qihong; Li, Kuan; Liu, Chuchu; Zhang, Huan; Zheng, Bingwen; et al.
Abstract: Endothelia progenitor cell (EPC)-based revascularization therapies have shown promise for the treatment of myocardial ischemic injury. However, applications and efficacy are limited by the relatively inefficient recruitment of endogenous EPCs to the ischemic area, while implantation of exogenous EPCs carries the risk of tumorigenicity. In this study, we developed a therapeutic protocol that relies on the capacity of neutrophils (NEs) to target lesions and release preloaded EPC-binding molecules for high efficiency capture. Neutrophils were loaded with superparamagnetic iron oxide nanoparticles conjugated to an antibody against the EPC surface marker CD34 (SPIO-antiCD34/NEs), and the therapeutic efficacy in ischemic mouse heart following SPIO-antiCD34/NEs injection was monitored by SPIO-enhanced magnetic resonance imaging (MRI). These SPIO-antiCD34/NEs exhibited unimpaired cell viability, superoxide generation, and chemotaxis in vitro as well as satisfactory biocompatibility in vivo. In a mouse model of acute myocardial infarction (MI), SPIO-antiCD34 accumulation could be observed 0.5 h after intravenous injection of SPIO-antiCD34/NEs. Moreover, the degree of CD133 + EPC accumulation at MI sites was three-fold higher than in control MI model mice, while ensuing microvessel density was roughly two-fold higher than controls and left ventricular ejection fraction was > 50%. Therapeutic cell biodistribution, MI site targeting, and treatment effects were confirmed by SPIO-enhanced MRI. This study offers a new strategy to improve the endogenous EPC-based myocardial ischemic injury repair through NEs mediated SPIO nanoparticle conjugated CD34 antibody delivery and imaging. Statement of Significance: The efficacy of endogenous endothelial progenitor cell (EPC)-based cardiovascular repair therapy for ischemic heart damage is limited by relatively low EPC accumulation at the target site. We have developed a method to improve EPC capture by exploiting the strong targeting ability of neutrophils (NEs) to ischemic inflammatory foci and the capacity of these treated cells to release of preloaded cargo with EPC-binding affinity. Briefly, NEs were loaded with superparamagnetic iron oxide nanoparticles conjugated to an antibody against the EPC surface protein CD34 (SPIO-antiCD34). Thus, we explored sites targeting with nanocomposites cargo for non-invasive EPCs interception and therapy tracking. We demonstrate that SPIO-antiCD34 released from NEs can effectively capture endogenous EPCs and thereby promote heart revascularization and functional recovery in mice. Moreover, the entire process can be monitored by SPIO-enhanced magnetic resonance imaging including therapeutic cell biodistribution, myocardial infarction site targeting, and tissue repair. Graphical abstract: Image, graphical abstract